Sistem Informasi Simpan Pinjam Berbasis Web Pada Koperasi Karyawan Bank Jambi - Nurhadi, Nurhadi; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2022)
Financial management at the Bank Jambi Employee Cooperative still uses a manual system using notebooks and Microsoft Excel. This method is less effective because the savings and loan transactions that occur are getting higher and more complex. With the increase in savings and loan transactions, the manual transaction settlement process takes a long time to validate from the loan application process, registration of new members and presentation of information related to member data, checking the amount of deposits, and loan reports which are carried out directly by visiting the cooperative office, thus causing delays in the management of the savings and loan transaction process stage and the presentation of information or reports produced is less than optimal.â€ The role of the system is to use Unified Modeling Language tools, to explain various functions of the system and produce a prototype of a savings and loan information system at the Bank Jambi Employee Cooperative. The design of this Savings and Loans information system is website-based. This web-based design of the Employee Cooperative Savings and Loans Information System of Bank Jambi can be used to improve the performance of the Bank Jambi Employee Cooperative because with this information system design, the recording of savings and loan transactions becomes faster and more accurate and reporting becomes easier and can also improve services to cooperative members, because members can apply for loans, view data on deposits, loans and installments online without having to come to the Bank Jambi Employee Cooperative office.